DELINEASI PROSPEK PANAS BUMI DI KAWASAN WISATA AIR PUTIH KABUPATEN LEBONG BENGKULU MENGGUNAKAN METODE MAGNETOTELURIK : GEOTHERMAL PROSPECT DELINEATION STUDY IN AIR PUTIH TOURISM AREA LEBONG DISTRICT BENGKULU USING MAGNETOTELLURIC METHOD - Della Zakia Soleha; Farid, Muchammad; Refrizon; Maesaroh, Rina; Hardianza, Meno; Hasugian, Basdiki; Gea, Jessica Agnes Soroinama; Al Ansory, Andre Rahmat (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2025)
Geothermal energy is renewable and can be used as an energy reserve in the future. This research aims to determine locations that have geothermal potential in the Air Putih Tourism area, Lebong Regency, Bengkulu Province based on resistivity values using the magnetoteluric method. The resistivity values obtained vary from low, medium, and high which can be used as a reference to describe subsurface conditions. In this data acquisition, measurements were made using the ADU-07e Magnetotelurik tool which has a measurement time of 16 hours with a low frequency bandwidth of 128 Hz, a medium frequency bandwidth of 1024 Hz, and a high frequency bandwidth of 4096 Hz. The sensor in the recording has two sensors: a magnetic sensor and an electrical sensor. The magnetic sensor consists of 3 sensors/coils (Hx, Hy, and Hz), while the electrical sensor uses 4 orthogonally placed pot shafts (Ex and Ey). Based on the results of data processing using the Magnetoteluric method with ZondMT software, there is a range of resistivity values of 10-700 (Ωm) which provides information on the structure of the subsurface layer. Layers with low resistivity (18-30 Ωm), medium resistivity (40-160 Ωm) and the highest resistivity (>300 Ωm).